KENDALA PENYULUH DALAM MELAKSANAKAN AKTIVITAS PENYULUHAN PADA USAHATANI KOPI DI KECAMATAN DEMPO UTARA KOTA PAGAR ALAM - Friatama Allen, Heru; Marli Batubara, Mustopa; Iswarini, Harniatun Iswarini (Societa: Jurnal Ilmu-Ilmu Agribisnis, 2015)
Extension Constrains In Implementing Education Activities In Coffe Farming In Dempo Utara District Pagar Alam City. This study aims to determine the constraints of agricultural extension in implementing education activities on a coffee farm in Dempo Utara District Pagar Alam City. The location of this research discovered accidentally by the consideration that at the location of the target area of Dempo Utaraagricultural extension centers and the majority of people seeking coffee farming. Field data collection was carried out from June to July 2015. The method used is a survey method, wherein the method is carried out to obtain the facts and phenomena that exist and these results can be represented on all the existing population and can apply in other regions. Methods of sampling done using census method. Respondents were taken is 6 agricultural extension of all the population extension. The results showed under theconstraints faced in implementing agricultural extension education activities at the coffee farm is within a residence with the location of activities, participation of farmers, and the extension means so very influential on education activities on a coffee farm in Dempo Utara District Pagar Alam City. Distance of residence to a location extension activities greatly affect the implementation of activities education on coffee farming, farmer participation is still lacking so difficult to gather farmer extension and counseling facilities that are stillincomplete so that the delivery of material less than the maximum in education activities at the coffee farm in Dempo Utara Pagar Alam City.